Long-channel InAlAs/InGaAs/InAlAs single-quantum-well MISFETs with subthreshold swing of 61 mV/decade and effective mobility of 11 900 cm2 V−1 · s−1. (8th May 2019) - Lee, In-Geun; Jo, Hyeon-Bhin; Yun, Do-Young; Shin, Chan-Soo; Lee, Jung-Hee; Kim, Tae-woo; Ko, Dae-Hong; Kim, Dae-Hyun
Abstract: We report In0.52 Al0.48 As/In0.7 Ga0.3 As/In0.52 Al0.48 As single-quantum-well metal-insulator-semiconductor field-effect transistors (MISFETs) with a selective source/drain regrowth process. Long-channel InGaAs MISFETs yielded a subthreshold swing (S) of 61 mV/decade at VDS  = 0.05 V and room temperature, and displayed very little frequency dispersion behavior in capacitance–voltage (CV) characteristics in both the strong-inversion and weak-inversion regimes. Both the S and CV results reflect the excellent interface quality between a molecular beam epitaxy-grown InAlAs insulator and an InGaAs channel. The devices showed as little as 0.8% per decade of frequency dispersion at the maximum gate capacitance in the strong-inversion regime. Moreover, the fabricated devices yielded an effective mobility ( μ n_ eff ) of 11 900 cm 2  V −1  · s −1 at room temperature, and degradation of μ n_ eff with V GS in the strong-inversion regime was negligible. These results are a consequence of the small interfacial state density and the smooth surface morphology at the interface.